2021
DOI: 10.1186/s40164-021-00202-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated coagulopathy: thromboembolism prophylaxis and poor prognosis in ICU

Abstract: Background Coronavirus disease 2019 (COVID-19) is associated with coagulation abnormalities which are indicators of higher mortality especially in severe cases. Methods We studied patients with proven COVID-19 disease in the intensive care unit of Jinyintan Hospital, Wuhan, China from 30 to 2019 to 31 March 2020. Results Of 180 patients, 89 (49.44 %) had died, 85 (47.22 %) had been discharged alive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Most patients have an air bronchogram 60 . The distribution characteristics of the abnormalities on X‐ray images about these five types of pneumonia are similar to those of CT images (slices) 52,61‐73 . Although the collected 2D data (e.g., X‐ray images) in our proposed data set misses lots of information (original intensity level, spacing, etc.)…”
Section: Proposed Covid‐19 Pneumonia Data Setmentioning
confidence: 75%
See 1 more Smart Citation
“…Most patients have an air bronchogram 60 . The distribution characteristics of the abnormalities on X‐ray images about these five types of pneumonia are similar to those of CT images (slices) 52,61‐73 . Although the collected 2D data (e.g., X‐ray images) in our proposed data set misses lots of information (original intensity level, spacing, etc.)…”
Section: Proposed Covid‐19 Pneumonia Data Setmentioning
confidence: 75%
“…60 The distribution characteristics of the abnormalities on X-ray images about these five types of pneumonia are similar to those of CT images (slices). 52,[61][62][63][64][65][66][67][68][69][70][71][72][73] Although the collected 2D data (e.g., X-ray images) in our proposed data set misses lots of information (original intensity level, spacing, etc.) than original volume data, considering the usage of our proposed 2D-oriented algorithm, we have tried our best to keep the original size of the images while avoiding the problem of image distortion.…”
Section: Data Set Creation and Structurementioning
confidence: 99%
“…Third, to determine COVID-19 associated thromboembolism, Sequential Organ Failure Assessment (SOFA) score that is one of the disease severity and organ failure scores has been evaluated by some previous studies. 4,5 These studies suggest that in critically ill COVID-19 patients, higher SOFA scores are associated with higher DVT frequency, D-dimer levels, duration of disease, hypoalbuminemia, and duration of disease. 4 Other previous study 5 reported that higher ISTH SIC scores which include SOFA score, prothrombin time-international normalised ratio (PT-INR), and platelet levels are associated with higher mortality and patients with ISTH SIC score higher than 3 had 3.05-fold increased mortality risk.…”
Section: Dear Editormentioning
confidence: 96%
“…Ten studies investigated the association of hypocalcemia with the same COVID-19 clinical outcomes (Table 1). [23,24,38,45,49,50,53,54,56,57] Majority of the studies defined hypocalcemia as having a serum calcium level of < 2.20 mmol/L, with the exception of one study that defined it as < 1.8 mmol/L. [56] There were no studies that investigated hypercalcemia.…”
Section: Dysnatremiamentioning
confidence: 99%